Transoral endoscopic thyroidectomy vestibular approach as a novel technique for pediatric populations: Results from a single surgeon - Ngo, Duy Quoc; Le, Duong The; Ngo, Quy Xuan; Van Le, Quang (Frontiers in Endocrinology, 2023)
Background The transoral endoscopic thyroidectomy vestibular approach (TOETVA) is increasingly being adopted worldwide because of its many advantages. However, there are few reports on the effectiveness and safety of TOETVA in children. In this study, we report the results of the application of TOETVA on 27 pediatric patients in Vietnam. To the best of our knowledge, this is also the largest sample size of the TOETVA technique performed by a single surgeon on pediatric patients worldwide. Patients and methods: From June 2020 to February 2022, we performed TOETVA on 27 pediatric patients (≤ 18 years old). The outcomes of the procedure were retrospectively reviewed. Results Our study was conducted on 27 pediatric patients, of whom 24 were female (88.9%). The mean age was 16.3 ± 2 (range 10-18). Fifteen patients had benign thyroid nodules with a mean nodule size of 31.6 ± 7.1 (range 20-50mm), and 12 patients had papillary thyroid carcinoma with a mean nodule size of 10.2 ± 5.6 (range 4-19mm). All 27 patients underwent successful TOETVA without any conversion to open surgery. The 15 patients with benign thyroid nodules had lobectomies with a mean operative time of 83.3 ± 10.5 (range 60-105 minutes). Among the 12 patients diagnosed with thyroid cancer, ten had a lobectomy, isthmusectomy, and central neck dissection, with a mean operative time of 89.8 ± 5.7 (range 80-100 minutes). The other two underwent total thyroidectomy with central lymph node dissection with a mean operative time of 132.5 minutes. The mean hospital stay was 4.7 ± 0.9 (range 3-7 days). No patient had permanent complications, such as hypocalcemia, recurrent laryngeal nerve injury, or mental nerve injury. The rates of temporary recurrent laryngeal nerve injury and mental nerve injury were 3.7% and 11.1% respectively. Conclusions TOETVA may be a feasible and safe surgical method for children with thyroid disease. However, we recommend that only high-volume thyroid surgeons with experience in TOETVA should perform TOETVA on the pediatric population.